Sexually transmitted infections : what we can't see [ (VEA Australia Pty Ltd, 2006)
This program combines an engaging story with the straight forward commentary from expert speakers; Doctor Cindy Pan and Phillip Patterson (Melbourne Sexual Health Clinic). In the style of the movie "Sliding Doors", we follow two different scenarios that look at the health consequences of a young couple's lifestyle decisions, and in the process present informationabout a range of sexually transmitted infections and the short and long term consequences of contracting them. Particular focus is paid to Chlamydia, Hepatitis B, PID, HIV, Genital Warts and Herpes, Pubic Lice and safe sex practices.